Middle Management and Instructional Leadership: The Case of Natural Sciences’ Heads of Departments in South Africa - Cynthia B Malinga; Loyiso C Jita; Abiodun A Bada (STKIP Singkawang, 2021)
Natural sciences heads of departments often find themselves in the middle, shuttling between one role as part of the school management team, and another as an ordinary classroom teacher whose role as subject and instructional leaders is made even more complex because of the several duties incorporated in the subject which brings together other science disciplines, with each having its own disciplinary culture and expectations. The crucial role played by this group of teachers in the area of management and instructional leadership can go a long way in determining effective output in teaching and learning. This study reports on a mixed methods approach to explore the practices of natural sciences heads of department, as they provide instructional leadership to the teachers in a multidisciplinary context of their subject. This research involved 30 participants who responded to the questionnaire and 6 purposively selected subject heads of department interviewed and observed from four districts in the Gauteng Province of South Africa. The data collected through questionnaire, semi-structured interview and observations were analysed using descriptive statistics and content analysis. The results from this investigation revealed that natural science heads of departments devise creative ways to mitigate the challenge of differently qualified natural science teachers. These study concludes that the effectiveness of heads of departments as instructional leaders is influenced by the immense pressure from the dual roles of managing from the middle, which also appear to affect the optimal implementation of the natural science curriculum.